SPORT AS AN ELEMENT OF DISTINCTION IN SOCIAL PHYSICAL EDUCATION CLASSES IN YMCA OF PERNAMBUCO (1902 - 1924). (Fiep Bulletin - online, 2011)
The History of Education, specifically physical education contributes to understanding the subsidies by which time spent on education in the early twentieth century. Taking as an element of physical education sport, there was a relationship between the practice of this activity, highly subject to controls, with the appearance of differentiation of recifense elite this period, circulated by the YMCA, an institution that has played key role in dissemination of sports in Brazil and worldwide. Through the use of concepts of the theory of Norbert Elias, also tried to demonstrate through the practice of Physical Education in Recife YMCA characteristics of the modernization process by which the city of Recife was passing, and indicate towards the use of religion and sports as elements related to control of pipelines and construction of the citizen that this new model of social relations needed, with greater control of his impulses and thus, with a greater level of self-control.
Keywords: YMCA; Recife; Physical Education